Optics of light scattering media : problems and solutions / Alexander A. Kokhanovsky. - Kokhanovsky, Alex A. (Springer-Praxis books in environmental sciences, 2001)
Covering modern knowledge of the optical properties of media in single and multiple light scattering regimes, such as snow, clouds and aerosols, this work may be used as a handbook by scientists from differing academic backgrounds.